2010
DOI: 10.1007/s00414-010-0503-z
|View full text |Cite
|
Sign up to set email alerts
|

Gunshot energy transfer profile in ballistic gelatine, determined with computed tomography using the total crack length method

Abstract: By measuring the total crack lengths (TCL) along a gunshot wound channel simulated in ordnance gelatine, one can calculate the energy transferred by a projectile to the surrounding tissue along its course. Visual quantitative TCL analysis of cut slices in ordnance gelatine blocks is unreliable due to the poor visibility of cracks and the likely introduction of secondary cracks resulting from slicing. Furthermore, gelatine TCL patterns are difficult to preserve because of the deterioration of the internal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 9 publications
0
15
0
3
Order By: Relevance
“…For gelatin the total crack length, i.e. the amount of fissures, can be assessed as an estimate of the wound damage by cutting or non-destructive imaging [47], [48].…”
Section: Introductionmentioning
confidence: 99%
“…For gelatin the total crack length, i.e. the amount of fissures, can be assessed as an estimate of the wound damage by cutting or non-destructive imaging [47], [48].…”
Section: Introductionmentioning
confidence: 99%
“…Rutty et al reported that the properties of gelatin blocks such as those used in our study make them an ideal model for investigations of the temporary wound cavity and possible cavitation effects [19]. The use of multi-slice CT imaging for detecting the presence of total crack lengths has been proved to be a reliable method of investigations of terminal ballistics [20]. Furthermore barium titanate particles in the wound allowed us to reliably analyze the contamination of wounds by exogenous particles and to determine the spatial distribution of these particles in relation to the bullet path.…”
Section: Discussionmentioning
confidence: 97%
“…The successful application of radiological imaging to ballistic models has been described by several groups [3,[5][6][7], and we already discussed the feasibility of using CT for the examination of ballistic head models [3]. However, it had not been put into practice before.…”
Section: Discussionmentioning
confidence: 98%